2008
DOI: 10.1002/bip.20883
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the native‐like properties of de novo designed cavitand‐based four‐helix bundle proteins

Abstract: We investigated the hydrophobic packing of two previously designed caviteins, LG2 and LG3, which differ by one Gly in the linker regions between the peptide sequence and the cavitand scaffold. We sought to diminish the putative native-like properties of LG2 and LG3, and see if we could diagnose a change in the conformational specificity of the hydrophobic core. We replaced the leucine residues with norleucine residues at the hydrophobic positions in LG2 and LG3, to create NG2 and NG3, respectively. LG2 exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 100 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…The calculated value of Δ G ° H 2 O for cavitein Q4 is −9.6 ± 0.6 kcal mol −1 . This is within error of the previously reported values for N1GG by Mezo and Huttunen (Table ). , …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The calculated value of Δ G ° H 2 O for cavitein Q4 is −9.6 ± 0.6 kcal mol −1 . This is within error of the previously reported values for N1GG by Mezo and Huttunen (Table ). , …”
Section: Resultssupporting
confidence: 91%
“…This is within error of the previously reported values for N1GG by Mezo and Huttunen (Table 1). 34,35 Concentration-dependent GuHCl unfolding experiments (high, 200 µM; low, 4 µM) were carried out to examine the aggregation state of Q4. 61 The high and low concentration studies showed indistinguishable denaturation curves, indicating that Q4 denatures cooperatively as a monomeric species (Figure 11).…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…The methyl shifts do not change the “hydrophobic content” of the peptide, but they can affect intermolecular peptide packing. As noted before, there is a difference in packing between Leu and Nle, in which Leu can pack more intimately than Nle 72 . As our crystal structure illustrates, the isobutyl side chains of Ile can interdigitate with each other to maximize hydrophobic interaction, a packing conformation inaccessible to Nle.…”
Section: Resultsmentioning
confidence: 54%